2012
DOI: 10.1111/j.1463-1318.2012.02943.x
|View full text |Cite
|
Sign up to set email alerts
|

ALEXIS O‐Ring wound retractor vs conventional wound protection for the prevention of surgical site infections in colorectal resections1

Abstract: The ALEXIS wound retractor is more effective in preventing SSI in elective colorectal resections compared with conventional methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
82
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(84 citation statements)
references
References 9 publications
2
82
0
Order By: Relevance
“…Several studies have demonstrated decreases in wound infection rates in open appendectomy, colon resection, and nontraumatic gastrointestinal surgery with the use of wound protection devices. 14 In contrast, Kercher found that plastic wound protectors did not affect wound infection rates following laparoscopically assisted colectomy in a retrospective study of 141 patients. 5 A recent meta-analysis of six randomized controlled trials representing 1,008 patients evaluating whether these wound protectors reduce the risk of surgical site infection (SSI) after gastrointestinal and biliary tract surgery found a significant decrease in the SSI rate with the use of a wound protector with a relative risk of 0.55 compared to unprotected wounds.…”
Section: Discussionmentioning
confidence: 96%
“…Several studies have demonstrated decreases in wound infection rates in open appendectomy, colon resection, and nontraumatic gastrointestinal surgery with the use of wound protection devices. 14 In contrast, Kercher found that plastic wound protectors did not affect wound infection rates following laparoscopically assisted colectomy in a retrospective study of 141 patients. 5 A recent meta-analysis of six randomized controlled trials representing 1,008 patients evaluating whether these wound protectors reduce the risk of surgical site infection (SSI) after gastrointestinal and biliary tract surgery found a significant decrease in the SSI rate with the use of a wound protector with a relative risk of 0.55 compared to unprotected wounds.…”
Section: Discussionmentioning
confidence: 96%
“…It also allows for improved exteriorization of bowel and mesenteric lymph nodes and prevents contamination of the wound margins, which has been shown in human studies to reduce wound infection rates. [26][27][28] …”
Section: Laparoscopic-assisted Procedures Of the Gastrointestinal Tractmentioning
confidence: 98%
“…This has become a frequently used equipment in laparoscopic anterior resection wherein big specimen needs to be delivered through a smaller incision akin to skin sparing mastectomy, due to its added advantage of being able to assist in retraction [11]. It is available in different sizes, large, medium and small [12].…”
Section: Introductionmentioning
confidence: 99%